Modelling relationships among students' inquiry-related learning activities, enjoyment of learning, and their intended choice of a future STEM career. Issue 1 (2nd January 2021) - Wang, Hsin-Hui; Lin, Huann-shyang; Chen, Ya-Chun; Pan, Yi-Ting; Hong, Zuway-R.
ABSTRACT: This study explored how specific inquiry-related learning activities were related to student enjoyment of learning science and intended choice of future STEM career. Analysis of Taiwan and Australia PISA 2015 data revealed that three activities, namely, debating and planning experiments, drawing conclusions and doing hands-on experiments, teachers and students explaining ideas, were significantly related to students' enjoyment of learning science and intended choice of STEM careers in these two countries. Cross-national comparisons indicated that the percentages of inquiry-related activities for high or low scientific competency students in Australia were higher than for Taiwanese students. The activity of teachers and students explaining ideas was a significant determinant of enjoyment of learning for Taiwanese high scientific competency students and Australian high and low scientific competency students, while debating and planning experiments was a positive determinant for Taiwanese low scientific competency students. High scientific competency students from both Taiwan and Australia demonstrated significantly higher preferences for future STEM careers than low scientific competency students.